Data Supporting GoodVibes: automated thermochemistry for heterogeneous computational chemistry data - Luchini, Guilian; Alegre-Requena, Juan V.; Paton, Robert S. (Zenodo, 2020)
These files are provided in support of the use case in a recent manuscript showing the use of the Python package GoodVibes . This data set contains Gaussian optimization and frequency calculations on 25 molecules, along with 25 corresponding ORCA single point energy calculations, a YAML file to dictate and format the reaction pathway, and example outputs of the tabulated thermochemistry and a PNG of the potential energy surface graph output. To generate these output files, the command: python -m goodvibes *.log --spc DLPNO --pes PhPy.yaml --graph PhPy.yaml -t 353.15 --imag --invertifreq -5 --media ethanol -c 1 was run in the directory containing the calculation output (.log and .out) files.